The large carpenter bee Xylocopa augusti (Hymenoptera: Apidae): New record for Chile - Montalva, Jose Miguel; Allendes, Juan L.; Lucia, Mariano (Journal of Melittology, 2013)
The large carpenter bee Xylocopa (Neoxylocopa) augusti Lepeletier de Saint Fargeau, 1841, is here recorded for the first time in Chile.  This new record increases to four the number of carpenter bees known for the country.  Host plant associations for X. augusti in Chile are provided.  A key to the species of Xylocopa Latreille in Chile as well as comments on the presence of X. (N.) bruesi Cockerell in the country are also presented.